Factores que influyen en la forma de la cola de un tsunami. - Chacón Barrantes, Silvia (2009)
The propagation speed of a tsunami depends on the depth of the ocean in which it propagates. As the tsunami crosses the abyssal plain, it suffers modifications in its form due to change in the depths of the ocean bottom. When the tsunami is reflected on coasts, islands or bathymetric discontinuities, the reflected wave is added to the original form of the tsunami. In this work it is identified how several factors affect the wave-form of a tsunami during its propagation through abyssal plains, by numerical simulations of a tsunami´s propagation from Alaska to Hawai.